Hydrophobic deep eutectic solvent (HDES) as oil phase in lipid-based drug formulations - Panbachi, Shaida; Beranek, Josef; Kuentz, Martin (International journal of pharmaceutics, 2024)
There is increasing pharmaceutical interest in deep eutectic solvents not only as a green alternative to organic solvents in drug manufacturing, but also as liquid formulation for drug delivery. The present work introduces a hydrophobic deep eutectic solvent (HDES) to the field of lipid-based formulations (LBF). Phase behavior of a mixture with 2:1 M ratio of decanoic- to dodecanoic acid was studied experimentally and described by thermodynamic modelling. Venetoclax was selected as a hydrophobic model drug and studied by atomistic molecular dynamics simulations of the mixtures. As a result, valuable molecular insights were gained into the interaction networks between the different components. Moreover, experimentally the HDES showed greatly enhanced drug solubilization compared to conventional glyceride-based vehicles, but aqueous dispersion behavior was limited. Hence surfactants were studied for their ability to improve aqueous dispersion and addition of Tween 80 resulted in lowest droplet sizes and high in vitro drug release. In conclusion, the combination of HDES with surfactant(s) provides a novel LBF with high pharmaceutical potential. However, the components must be finely balanced to keep the integrity of the solubilizing HDES, while enabling sufficient dispersion and drug release.
Keywords: Surface-Active Agents; Drug Compounding; Polysorbates; simulace molekulární dynamiky; Lipids; sulfonamidy; polysorbáty; Lauric Acids; Drug Liberation; příprava léků; Solubility; rozpustnost; Oils; uvolňování léčiv; farmaceutická chemie; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions; Solvents; lipidy; Chemistry, Pharmaceutical; Sulfonamides; oleje; Molecular Dynamics Simulation; rozpouštědla; povrchově aktivní látky; kyseliny laurové